Improving the Quality of National Education Through the Integrity of Educational Psychology in the Curriculum - Erni Ratna Dewi; Kandi Kandi; Lela Nurlaila (Gestion Educativa, 2025)
This study aims to analyze the integration of educational psychology into the curriculum as a strategy to improve the quality of national education. The background of this study is based on the fact that the quality of education in Indonesia still faces various challenges, particularly in aspects of learning motivation and student psychological development. This study uses a descriptive qualitative approach with a case study method, where data are collected through in-depth interviews, observations, and documentation studies of teachers, principals, and students in several secondary schools that have implemented psychological approaches in learning. The results show that the integration of educational psychology into the curriculum can increase student participation, create a more conducive learning environment, and encourage a more balanced academic and non-academic achievement. However, its implementation still faces obstacles such as limited teacher training and a lack of explicit policy support. Therefore, strengthening the capacity of educators and more systematic policies are needed to realize a curriculum that is holistic and responsive to the psychological needs of students.